Varying Approaches to Readability Measurement - Chall, Jeanne (Revue québécoise de linguistique)

(untitled) (Université du Québec à Montréal, 1996)
ABSTRACTThe article discusses the three approaches to readability measurement that have been developed from the early 1900s to the présent—classic readability, cognitive-structural readability, and judgment-qualitative approaches. The classic approaches to readability are the most widely used. They use similar text features to predict readability—some aspects of word difficulty and some measure of sentence complexity. The cognitive-structural approaches are concerned more with the structure of a text and its meaning. The judment-qualitative approaches do not rely on specific features but on a qualitative judgement of overall difficulty.Each of these approaches is further treated in terms of its underlying theories, the text features and characteristics mesured, its reliability and validity and its practical uses.